Analysis of Environmental Risk Factors Associated with Malaria Incidence in Papua, Indonesia - Ashar, Yulia Khairina; Lauchan, Agil Maritho; Safira , Putri (Universitas Airlangga, 2025)
Introduction: Papua is the region with the highest malaria burden in Indonesia, accounting for about 84% of the total national malaria cases. The high incidence rate indicates the need for a multidimensional approach, including analysis of environmental determinants. Therefore, this study aimed to evaluate the influence of environmental risk factors on the incidence of malaria in Papua, Indonesia. Methods: A cross-sectional observational design was used based on secondary data from the 2023 Indonesian Health Survey. The analysis was conducted on 37,987 respondents using Chi-square test and binary logistic regression. The variables analyzed included housing conditions, physical quality of water, wastewater drainage systems, and waste management. Results and Discussion: The results showed that, based on bivariate analysis, four environmental factors were significantly related to malaria incidence (p<0.05). However, in the multivariate analysis, only three variables remained significant, wastewater drainage system (OR=1.203; p<0.001), poor waste management practices (OR=1.103; p<0.016), and housing conditions (OR=0.884; p<0.001). while water quality had no significant effect. Conclusion: These findings highlight the importance of incorporating environmental management into malaria control strategies, especially in endemic and resource limited regions like Papua, through multisectoral collaboration between health and environmental authorities.